2021
DOI: 10.1017/s0022050721000322
|View full text |Cite
|
Sign up to set email alerts
|

From Material to Non-Material Needs? The Evolution of Mate Preferences through the Twentieth Century in France

Abstract: This paper studies the evolution of mate preferences throughout the twentieth century in France. I digitized all the matrimonial ads published in France’s best-selling monthly magazine from 1928 to 1994. Using dictionary-based methods, I show that mate preferences were mostly stable during the Great Depression, WWII, and the ensuing economic boom. These preferences started transforming in the late 1960s when economic criteria were progressively replaced by personality criteria. The timing coincides with profou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…In contrast, the availability of other romantic partners may be more important in the separation decision, since initiation is very predictive of the likelihood of finding a new partner, which in turn is strongly linked to other outcomes. Such an interpretation would also be consistent with recent evidence showing a decline in the importance of economic factors vis-à-vis nonmaterial needs when searching for a romantic partner ( 86 ).…”
Section: Discussionsupporting
confidence: 89%
“…In contrast, the availability of other romantic partners may be more important in the separation decision, since initiation is very predictive of the likelihood of finding a new partner, which in turn is strongly linked to other outcomes. Such an interpretation would also be consistent with recent evidence showing a decline in the importance of economic factors vis-à-vis nonmaterial needs when searching for a romantic partner ( 86 ).…”
Section: Discussionsupporting
confidence: 89%
“…Both human [ 49 ] and animal [ 50 ] studies show females mimic others’ mate choices and preferences. Cultural shifts, like Western societies moving from material to non-material priorities [ 25 ], could hasten and strengthen these changes through imitation, potentially creating distinct between-population differences fueled by social learning [ 51 ].…”
Section: Discussion and Conclusionmentioning
confidence: 99%
“…Mate preferences also seem to change in societies over time, even within the relatively short time span of years or a few decades. A study about women’s matrimonial ads in France found that mate preferences were relatively stable from the 1920s through the 1960s, when the critical importance of material needs started decreasing and the importance of personality criteria started increasing again [ 25 ]. A study by Lu et al [ 26 ] highlighted the influence of economic situation on the mate preferences of females.…”
Section: Introductionmentioning
confidence: 99%
“…Mate preferences seem also to change in societies over time, even within the relatively short time span of years or a few decades. A study about women's matrimonial ads in France finds that mate preferences are relatively stable from the 1920s through the 1960s, when the critical importance of material needs started decreasing and the importance of personality criteria started increasing again (Lippmann, 2021). A study by Lu et al (2015) highlights the influence of the economic situation on mate preferences of females.…”
Section: Testing Sexual Strategy Theory In Norway Introductionmentioning
confidence: 99%